2013
DOI: 10.1371/journal.pone.0063329
|View full text |Cite
|
Sign up to set email alerts
|

Murine Bone Marrow Lin−Sca-1+CD45− Very Small Embryonic-Like (VSEL) Cells Are Heterogeneous Population Lacking Oct-4A Expression

Abstract: Murine very small embryonic-like (VSEL) cells, defined by the Lin−Sca-1+CD45− phenotype and small size, were described as pluripotent cells and proposed to be the most primitive hematopoietic precursors in adult bone marrow. Although their isolation and potential application rely entirely on flow cytometry, the immunophenotype of VSELs has not been extensively characterized. Our aim was to analyze the possible heterogeneity of Lin−Sca+CD45− population and investigate the extent to which VSELs characteristics m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 59 publications
3
47
0
1
Order By: Relevance
“…Recently, several groups have reported that they have been unable to isolate VSEL cells and suggest that there are insufficient animal data to warrant human clinical trials [28][29][30]. There is no doubt that isolation of VSEL cells and their cultivation is a difficult endeavor.…”
Section: Fig 4 Huvsel Osseous Repair Of Craniofacial Defects (A)mentioning
confidence: 99%
“…Recently, several groups have reported that they have been unable to isolate VSEL cells and suggest that there are insufficient animal data to warrant human clinical trials [28][29][30]. There is no doubt that isolation of VSEL cells and their cultivation is a difficult endeavor.…”
Section: Fig 4 Huvsel Osseous Repair Of Craniofacial Defects (A)mentioning
confidence: 99%
“…Thus, their pluripotency should be reproducible in independent laboratories, a requirement for a scientific finding to be generally accepted (Jasny et al., 2011). However, recent studies have shown the lack of stem cell characteristics in VSELs isolated from mouse (Szade et al., 2013) or human cord blood (CB) (Danova-Alt et al., 2012), while another study confirmed the existence of mouse VSELs and their ability to give rise to lung cells (Kassmer et al., 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Is one set of ideas going to triumph about the existence of VSELs or will there eventually be a resolution where both sides' hypotheses contain aspects that are correct? I actually don't think we know yet, but publications showing evidence for VSELs are cropping up in good journals [5][6][7][8][9]. That said, I do believe finding our way through this controversy has a ''going to be fun to watch'' outlook written all over it.…”
mentioning
confidence: 97%